Potential of natural products as radioprotectors and radiosensitizers: opportunities and challenges. Issue 12 (21st May 2021) - Yi, Juanjuan; Zhu, Jiaqing; Zhao, Changcheng; Kang, Qiaozhen; Zhang, Xiaomiao; Suo, Keke; Cao, Nana; Hao, Limin; Lu, Jike
Abstract : Natural products can be used as natural radiosensitizers and radioprotectors, showing promising effects in cancer treatments in combination with radiotherapy, while reducing ionizing radiation damage to normal cells. Abstract : Natural products can be used as natural radiosensitizers and radioprotectors, showing promising effects in cancer treatments in combination with radiotherapy, while reducing ionizing radiation (IR) damage to normal cells/tissues. The different effects of natural products on irradiated normal and tumor cells/tissues have attracted more and more researchers' interest. Nonetheless, the clinical applications of natural products in radiotherapy are few, which may be related to their low bioavailability in the human body. Here, we displayed the radiation protection and radiation sensitization of major natural products, highlighted the related molecular mechanisms of these bioactive substances combined with radiotherapy to treat cancer, and critically reviewed their deficiency and improved measures. Lastly, several clinical trials were presented to verify the clinical application of natural products as radiosensitizers and radioprotectors. Further clinical evaluation is still needed. This review provides a reference for the utilization of natural products as radiosensitizers and radioprotectors.